Teologi Al-Ma'un Berperspektif Perempuan: Pemberdayaan Ekonomi Perempuan Pekerja Rumah Tangga Keliling di Tangerang Selatan: indonesia - Pratiwi, Aina Wulan; Fadillah, Laila; Anggraini, Elsa; Destiana, Puspa Dwi; Asari, Hafizh Ihsan; Sujatna, Yayat (UII, 2025)
Aisyah (52 years old) works as a non-permanent domestic worker (PRT) earning a wage of IDR 500,000 per month. To meet the economic needs of her family with a husband who has been ill for years and is senile, two children, three grandchildren under the age of 10, and one unemployed son-in-law, Aisyah also has to work as an itinerant domestic worker in many of her neighbours' homes. However, with an average income of no more than IDR 1,000,000 per month, it is still not enough to fulfil her family's needs. Aisyah is the most underprivileged family, as a woman who is the backbone of the family found in the Legoso neighbourhood, East Ciputat, South Tangerang based on the results of observations and village maps with the community with 30 indicators of ‘Theology of Al-Maun with Women's Perspective/Feminism (TABP/F)’ which has been developed since 2017 on the campus of the Ahmad Dahlan Institute of Technology and Business Jakarta (ITB-AD). This community service was carried out using the TABP/F methodology, raising funds by selling, which was carried out by group five, semester five, accounting study programme ITB-AD Jakarta for one semester. As a result, the funds collected were used to open selling a seblak and fried food stall as Aisyiyah's effort to increase economic income located in front of her house. Aisyiyah also received training in business management such as calculating capital, production or selling costs, prices, and income. After the business was open for one month and accompanied by the sales process, there was a significant increase in Aisyiyah's monthly income reaching IDR 800,000. Aisyah was also taught how to calculate zakat if her business had progressed. The challenges: the sustainability of Aisyah's business without assistance, as well as the high habit of borrowing from neighbours when buying snacks.